Broadband access in Korea experience and future perspective. - Lee, Yong-Kyung (IEEE Communications magazine)
With the growing popularity of the Internet, Korea has been successful in providing broadband Internet services to the level of universal service. More than 70 percent of households have high-speed Internet connection, and their lives have been changed dramatically. The cutting edge technology of broadband Internet has a profound impact on many aspects of the economy, education, entertainment, and social culture. This article addresses the experiences and future perspectives of KT (formerly Korea Telecom) in providing the broadband network and services in Korea. We present our experiences in the deployment of the world's largest ADSL network, and our ongoing deployment of VDSL and WLAN. Based on the accomplishment in broadband access, we also provide a forecast on the next generation of broadband services and the corresponding technologies required to support these services.